Community-level contextual factors associated with lung cancer: a hot spot analysis - Taylor Jansen; Qian Song; Kristie Long Foley; Elizabeth Dugan (Cancer Causes & Control, 2026)

Radiocarbon and luminescence age estimate database for the Willandra Lakes Region World Heritage Area: a reliability-assurance assessment - Nathan R. Jankowski; Nicola Stern; Elizabeth Foley; Geraldine Jacobsen; Haidee Cadd; Tegan Smith (Quaternary Geochronology, 2025)

Time allocation to balance group living trade-offs in Ethiopian wolves - Elisa Sandoval-Serés; James Foley; Elizabeth Preston; Edris Ebu; Jorgelina Marino (Behavioral Ecology and Sociobiology, 2023)
Living in groups requires individuals to make trade-offs to maintain group cohesion and enhance individual and inclusive fitness. One way animals can do this is by adjusting the way they allocate time to different behaviours. Ethiopian wolves ( Canis simensis ) are highly social, cooperative breeders (only the dominant pair breeds and all members help to raise the litter), but solitary foragers. To investigate how Ethiopian wolves allocate their time to balance the costs and benefits of group living, we analysed the time budgets of 47 wolves across six behaviours. We hypothesized that group size and territory density would affect wolves’ time allocation between solitary (foraging) and communal activities (patrolling and socialising) differently in relation to their age, dominance status or sex, and whether the pack was breeding or not. Our results showed that the time spent foraging alone increased at higher territorial densities, as expected from interference competition, particularly among subadults, subordinates and individuals in breeding packs. On the other hand, as pack size increased, adult wolves spent a lower proportion of time patrolling, while the time spent socialising did not change. Living in groups reduces the costs of communal activities, but crowded territories come at the cost of interference competition for solitary foragers, particularly the animals further down the hierarchy ranks, subadults, and individuals investing in breeding. Such trade-offs could impose an upper limit to group size and population growth within a limited space. Furthermore, anthropogenic disturbance could alter the balance of social and solitary activities of Ethiopian wolves.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

An assessment of the potential impacts of climate change on freshwater habitats and biota of Indiana, USA - Tomas O. Höök; Carolyn J. Foley; Paris Collingsworth; Leslie Dorworth; Brant Fisher; Jason T. Hoverman; Elizabeth LaRue; Mark Pyron; Jennifer Tank (Climatic Change, 2020)

Trans-Tasman Cumulative Effects Management: A Comparative Study - Kathryn K. Davies; Karen T. Fisher; Gemma Couzens; Andrew Allison; Elizabeth Ingrid van Putten; Jeffrey M. Dambacher; Melissa Foley; Carolyn J. Lundquist (Frontiers in Marine Science, 2020)

The sigma-1 antagonist BMY-14802 inhibits L-DOPA-induced abnormal involuntary movements by a WAY-100635-sensitive mechanism - Melanie A. Paquette; Katherine Foley; Elizabeth G. Brudney; Charles K. Meshul; Steven W. Johnson; S. Paul Berger (Psychopharmacology, 2009)

The sigma-1 antagonist BMY-14802 inhibits L-DOPA-induced abnormal involuntary movements by a WAY-100635-sensitive mechanism - Melanie A. Paquette; Katherine Foley; Elizabeth G. Brudney; Charles K. Meshul; Steven W. Johnson; S. Paul Berger (Psychopharmacology, 2009)